Effect of production system on physical–chemical, antioxidant and fatty acids composition of Longissimus dorsi and Serratus ventralis muscles from Iberian pig (Food Chemistry, 2012)
The effect of three production systems of Iberian pigs namely Montanera (free-range system and feeding based on acorns and grass), Recebo (free-range system and nutrition based in combination of acorns, grass and mixed feeds) and Intensive (conﬁnement with mixed feeds) on some quality traits of Longissimus dorsi (LD) and Serratus ventralis (SV) muscles were studied. Muscles from pigs raised in the Montanera system showed signiﬁcantly higher CIE L ⁄ , a ⁄ and b ⁄ values and higher haem pigment content than those from Intensive system. Similarly, muscles from pigs raised in the Montanera system had signiﬁcantly higher contents of a and c-tocopherol and phenolic compounds contents and higher lipophilic and hydrophilic activity antioxidant than those from pigs raised in the Intensive system. Fatty acids proﬁles from Montanera pigs had signiﬁcantly higher monounsaturated (MUFA) and polyunsaturated (PUFA) fatty acids and lower saturated fatty acids (SFA) than those from pigs raised in the Intensive system. In relation to muscle effect, LD showed lower intramuscular fat (IMF), a-tocopherol, phenolic compounds, lipid oxidation and PUFA, but higher MUFA than SV.

Study of variability in antioxidant composition and fatty acids profile of Longissimus dorsi and Serratus ventralis muscles from Iberian pigs reared in two different Montanera seasons. (Meat science, 2012)
This investigation was designed to evaluate the effects of variations in antioxidant and fatty acids composition of acorns and grass from two Montanera (free-range system and feeding based on acorns and grass) seasons (2006/07 and 2007/08) on the antioxidant composition and fatty acids profile of m. Longissimus dorsi (LD) and m. Serratus ventralis (SV) from Iberian pigs reared under these Montanera seasons. Acorn and grass composition was affected by Montanera season and consequently, LD and SV muscles showed different contents of α-tocopherol, total phenols, hydrophilic and lipophilic antioxidant activity and fatty acid profile, according with the composition of acorns and grass ingested. Results suggest a lack of uniformity in meat quality between different seasons. This could be due to the variable nature of extensive pig production as reflected in the variability in the composition of the diet (acorns and grass).

Fenofases florales en quercus rotundifolia lam. (II Congreso Forestal Español, 1997)
In this work the floral stages are introduced that it is happened in the masculine and feminine flowering of the holm-oak (Quercus rotundifolia Lam.). In each described stages they incorporate data on the floral morphology: state of development that it reach the catkins, the floral group and the tlowers. Also data of the receptive state in the are inserted feminine tlowers and ripening and viability grade of the grain of ponen and ovule. Finally is represented in a graphic each one of the described stage. K.W.:

FORESTACIÓN CON CUATRO ESPECIES (Quercus coccifera L., Q.faginea Lam., Q. rotundifolia y Q. suber L.) DE FRONDOSAS EN EXTREMADURA P.M. (II Congreso Forestal Español, 1997)
The principal species of interest in order to form forests of mediterranean type (not of riverside) in the South half of the Iberian Peninsula are the genus Quercus L ones. In this work the outputs contrasted of development are introduced, 1 root and systems of protection utilized in a mixed afforestation with four species of the cited genus (Q. coccifera L., Q. faginea Lam., Q. rotundifolia Lam., Q. suber L.), in Extremadura (Spain). The analysis of the data offers different strategies in sylviculture for the forest recuperation of the zone in function of the species that utilize

Medicinal plants used in the Barros Area, Badajoz Province, Spain. (Journal of ethnopharmacology, 1997)
A study of the wild and cultivated medicinal plants used in the Barros Area (southern Spain) is reported, 48 plants distributed among 20 different families are used in the treatment of various human diseases. The use of Bellis annua L. Centaurea ornata Wild., Leuzea conifera (L.) DC., Pulicaria paludosa Link and Asparagus aphyllus L. is reported.
From Duplicate 2 (Medicinal plants used in the Barros Area, Badajoz Province, Spain. - Vázquez, F M; Suarez, M a; Pérez, A)

PRODUCCION DE BELLOTA EN QUERCUS ROTUNDIFQLIA LAM.: VARIABILIDAD ANUAL E IMPORTANCIA ECONOMICA (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
The acorn production on Q. rotundifolia Lam. has been analyzed from 1989 through 1992 in Extremadura. The efects of different areas, each tree, and the interaction between areas/years are significatives. Genetic, pruning, environment and phytosanitary factors are the possible causes of these differences. Finally, the econornic efects of acorn production on iberian pig feeding (Montanera) has been studied. This is the rnain factor for high quality products.